Cigarettes demand and tax strategy in Malaysia - Mohamed Nor, Norashidah; Raja Abdullah, Nik Mustapha; Y., Mastura (Universiti Putra Malaysia Press, 2013)
Taxation is one of the effective tools to discourage smoking. Increase of cigarette tax has a significant effect in generating additional revenue to the government due to the inelastic nature of the cigarette. In this study, the estimated price elasticity of demand for cigarettes in Malaysia is -0.28 and -0.49 in short run and long run; respectively. Hence, demand for cigarettes is inelastic or less responsive to the changes in price. Therefore, estimating the optimal cigarette tax rate is one of the strategies to ensure that the price of cigarette, after tax, is high enough to reduce consumption of cigarette. At the same time, it generates maximum tax revenue for the government. Using yearly time series data from 1980 until 2009, a Fully Modified Ordinary Least Square (FMOLS) method is applied to estimate the demand elasticity of cigarettes and the optimal cigarettes excise tax. In this study, the estimated optimal real excise tax rate is 0.186 sen per stick which is 27.4% higher than the real excise tax in 2009. The increase in real revenue earned after imposing an optimal excise tax is 24.25% in the short run and 21.89% in the long run. Consequently, the expected reduction in consumption per capita of cigarette is 10.41% in the short run and 12.88% in the long run. Maximum revenues from the optimal cigarettes tax can be earmarked to fund a specific tobacco control policy in Malaysia.